Sorption thermal energy storage: Hybrid coating/granules adsorber design and hybrid TCM/PCM operation. (15th March 2019) - Engel, Georg
Highlights: A hybrid coating/granules adsorber design is introduced for thermal energy storage. A hybrid TCM/PCM operation is proposed for heating applications. Experimental results for charging and discharging, heating and cooling. An average cooling power of 1.05(8) kW within 30 min. An average heating power of 1.33(6) kW within 30 min in TCM/PCM operation. Abstract: A novel adsorber design combining fin-coating and filling of granules between the fins is introduced for closed sorption thermal energy storage. A storage system is designed and assembled, experimental results are presented for charging and discharging, heating and cooling. Considering the use case of the thermal management of the battery in a hybrid vehicle, a total cooling energy of 544(8) Wh in a period of 30 min is measured, which gives an average cooling power of 1.05(8) kW. A novel hybrid operation mode is proposed for discharging the storage for heating purposes, exploiting the features of both phase-change and thermochemical materials simultaneously by allowing water to freeze in the evaporator. The freezing enthalpy can then be exploited as evaporation enthalpy, removing the need for an external low-temperature heat source for the evaporator. This hybrid operation might be beneficial, e.g. in winter in order to preheat the battery before discharging it.